Analisis Pemungutan Pajak Bumi dan Bangunan Perkotaan di Kota Semarang Tahun 2012-2013 - M N Istiyanto Aji; Dzunuwanus Ghulam Manar; Wiwik Widayati (Journal of Politic and Government Studies, 2014)
The background of this study of fiscal decentralization policy implemented by the government, particularly in the transfer of authority collection urban land and building tax from Central Government to the Government of Semarang in 2012, the authority in carrying out urban land and building tax collection entirely within the current city government Semarang, because urban land and building tax into local tax revenues and the whole result is the original income Semarang. However, a decline in revenue target urban land and building tax after becoming local taxes in the city of Semarang in 2012-2013. The purpose of this study is to describe and analyze collection urban land and building tax in the city, the factors causing the decline in revenue target urban land and building tax in Semarang as well as the efforts made by the government of Semarang to increase acceptance urban land and building tax.This study is a qualitative research, technique of data collection by interviews, documentation and literature. Results of the study was a decrease in revenue target urban land and building tax in Semarang City year 2012-2013 resulting from the lack of preparedness of Semarang City Government in implementing the transfer of urban land and building tax became local taxes. Among others of the organizational structure and working procedures of implementing the collection is too simple, human resources are less than in quantity and quality, base data held is not accurate, the supporting infrastructure is not well established, as well as the collection system that does not comply with the rules determined.